Age-dependent loss of Crls1 causes myopathy and skeletal muscle regeneration failure - Yoo, Youngbum; Yeon, MyeongHoon; Kim, Won-Kyung; Shin, Hyeon-Bin; Lee, Seung-Min; Yoon, Mee-Sup; Ro, Hyunju; Seo, Young-Kyo (Experimental & molecular medicine, 2024)
Skeletal muscle aging results in the gradual suppression of myogenesis, leading to muscle mass loss. However, the specific role of cardiolipin in myogenesis has not been determined. This study investigated the crucial role of mitochondrial cardiolipin and cardiolipin synthase 1 (Crls1) in age-related muscle deterioration and myogenesis. Our findings demonstrated that cardiolipin and Crls1 are downregulated in aged skeletal muscle. Moreover, the knockdown of Crls1 in myoblasts reduced mitochondrial mass, activity, and OXPHOS complex IV expression and disrupted the structure of the mitochondrial cristae. AAV9-shCrls1-mediated downregulation of Crls1 impaired muscle regeneration in a mouse model of cardiotoxin (CTX)-induced muscle damage, whereas AAV9-mCrls1-mediated Crls1 overexpression improved regeneration. Overall, our results highlight that the age-dependent decrease in CRLS1 expression contributes to muscle loss by diminishing mitochondrial quality in skeletal muscle myoblasts. Hence, modulating CRLS1 expression is a promising therapeutic strategy for mitigating muscle deterioration associated with aging, suggesting potential avenues for developing interventions to improve overall muscle health and quality of life in elderly individuals. Mitochondrial Cardiolipin: The Unsung Hero in Age-Related Muscle Deterioration Aging often results in a decrease in muscle mass and function, a condition called sarcopenia. This research examines the role of a protein found in mitochondria (the energy factories of cells), cardiolipin synthase 1 (CRLS1), in muscle health and aging. The scientists discovered that levels of CRLS1 and cardiolipin, a fat it produces, decrease in the muscles of older mice. When CRLS1 levels were artificially lowered in young mice, their muscle mass and strength reduced. On the other hand, increasing CRLS1 levels in older mice improved muscle mass and strength. The research also found that CRLS1 is essential for muscle cell development and mitochondrial function. These results suggest that CRLS1 could be a potential treatment target for sarcopenia. More research is needed to further understand the metabolic changes caused by CRLS1 regulation. This summary was initially drafted using artificial intelligence, then revised and fact-checked by the author.